Prevalence of Malocclusions and Associated Factors inBrazilian Children and Adolescents with CerebralPalsy: A Multi-Institutional Study - Andreia Medeiros Rodrigues Cardoso; Clara Regina Duarte Silva; Lays Nóbrega Gomes; Mariana Marinho Davino de Medeiros; Wilton Wilney Nascimento Padilha; Alidianne Fábia Cabral Cavalcanti; Alessandro Leite Cavalcanti (Hindawi Limited, 2020)
Background. To assess the prevalence and factors associated with malocclusions in children and adolescents with cerebral palsy (CP). Methods. The study included 134 subjects with CP aged 2-18 years enrolled in six rehabilitation institutions and their caregivers, which provided demographic, systemic, and behavioral data. A calibrated researcher held oral examinations with record of the following malocclusion indexes, DAI and DMFT. Poisson regression analysis was used (α < 0.05). Results. About 85.8% (n = 115) of patients had malocclusion. In deciduous and mixed dentition (n = 99), increased overjet (75.8%), open bite (51.5%), posterior cross bite (19.2%), and anterior cross bite (3.0%) were identified. Increased overjet was associated with the age group of 2-5 years and mild communication impairment. Anterior open bite was more common in children who underwent tongue interposition, lip interposition, and pacifier sucking. Communication skills, mouth breathing, and tongue interposition were associated with posterior cross bite. Severe malocclusions (DAI > 30) were observed in 88.6% of patients with permanent dentition (n = 35) and were associated with liquid diet consistency and finger sucking. Conclusion. The prevalence of malocclusion in individuals with CP was high and associated with demographic, behavioral, and systemic factors.